SINDROMA NEUROLEPTIK MALIGNA: LAPORAN KASUS JARANG - said, sari (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
ABSTRACT Background: Malignant Neuroleptic Syndrome (SNM) is a rare syndrome, around 0.01% to 3.3%, patients who experience SNM are often occurring at a young age male (2:1). SNM has 4 symptoms, namely hyperpyrexia, muscle rigidity, mental changes, and autonomic instability. Case Report: MI, 16 years old, with slurred speech 3 days before going to the hospital. The patient had a history of being hospitalized with a psychiatrist for 2 days with Risperidone 2x1mg and Haloperidol 2x5mg as home medications. There are significant findings in leukocytosis (19,500) and an increase in liver enzymes (SGPT 65). On the 7th day of treatment, the patient who was initially rowdy, restless, and spoke slurred suddenly experienced symptoms of being unable to move, drooling a lot accompanied by not being able to swallow, then haloperidol 2x2.5mg was stopped and showed a gradual improvement in his condition. Discussion: Malignant neuroleptic syndrome is rare but can cause morbidity and mortality. On MI examination there was leukocytosis (19,000) and an increase in liver enzymes (SGPT 65), this is to research conducted by Micheal Kiyingi, et al. (2020) which states that patients diagnosed with SNM will experience leukocytosis and elevated liver enzymes. There are no guidelines for the management of SNM, but our patient stopped taking risperidone and haloperidol and gradually improved clinically. This is to the research of Ling Deng, et al (2022) which stated that risperidone and haloperidol can cause SNM, so, in the treatment of SNM, these drugs must be discontinued. This case shows that early and appropriate diagnosis and management in SNM cases are very important to obtain good clinical outcomes and avoid misdiagnoses that result in disability and death. Keywords: Malignant Neuroleptic Syndrome, antipsychotic, pediatric